3 - Désindustrialìsation et crise de société en Algerie: by Said Chikhi - Said Chikhi, (Africa Development, 1991)
Abstract: Algeria is going through a severe crisis in the late 1980s . Yet, analyses undertaken tend to see it merely as a socio-economic result of the crisis of the world economic and financial market. Now , the predominance of external economic factors should not veil internal state economic policy-related factors , the incapacity of the political system to change social actors into agents involved in the economic and social recovery processus. Nor should it hide the different forms of intervention of such social and political actors in the crisis. These factors have had a negative impact on the state-controlled industrial sector on which the country's development policy is hinged. As a result , a de-industrialization process has started , ending up in more unemployment , a dismembering of society and a marginalizai ion of social actors. Given this environment , it is no wonder that the religious machinery gathered speed and tried to replace the state apparatus with a view to managing the social arena as rigidly as would a religious s